Molecular mechanisms of diabetic cardiomyopathy - Bugger, Heiko; Abel, E. Dale (Diabetologia, 2014)
In recent years, diabetes mellitus has become an epidemic and now represents one of the most prevalent disorders. Cardiovascular complications are the major cause of mortality and morbidity in diabetic patients. While ischaemic events dominate the cardiac complications of diabetes, it is widely recognised that the risk for developing heart failure is also increased in the absence of overt myocardial ischaemia and hypertension or is accelerated in the presence of these comorbidities. These diabetes-associated changes in myocardial structure and function have been called diabetic cardiomyopathy. Numerous molecular mechanisms have been proposed to contribute to the development of diabetic cardiomyopathy following analysis of various animal models of type 1 or type 2 diabetes and in genetically modified mouse models. The steady increase in reports presenting novel mechanistic data on this subject expands the list of potential underlying mechanisms. The current review provides an update on molecular alterations that may contribute to the structural and functional alterations in the diabetic heart.